THE INFLUENCE PERCEIVED QUALITY, BRAND TRUST AND CUSTOMER EXPERIENCE ON REPURCHASE INTENTION OF SKINTIFIC PRODUCTS - Adela Aurelia Kinaya Dewi; Yanda Bara Kusuma (Universitas KH. Abdul Chalim Mojokerto, 2025)
The competitive landscape in the beauty industry in Indonesia is increasing significantly, along with the growing consumer awareness and interest in high-quality skincare products. One brand that has recently begun to attract attention, especially among urban communities such as in Surabaya City, is Skintific. This study analyzes how customer experience, brand trust, and perceived quality affect consumers' intentions to repurchase Skintific products. A sample of Surabaya City residents who use Skintific products is used in this quantitative investigation. The study involved 100 participants, selected through a purposive sampling method as part of a non-probability sampling approach. Online questionnaires were distributed in order to collect data. Several linear regression analyses were performed using SPSS version 30 software. The results show that the three independent factors, perceived quality, brand trust, and customer experience, all have a positive significant impact on repurchase intention, both simultaneously and individually. These findings show that views of product quality, trust in the brand, and a great customer experience are important factors in increasing consumers' desire to repurchase Skintific products in a highly competitive market.